2000
DOI: 10.1007/bf03024869
|View full text |Cite
|
Sign up to set email alerts
|

“Deep-forehead” temperature correlates well with blood temperature

Abstract: We have demonstrated that the "deep-forehead" temperature has excellent accuracy and clinically sufficient precision as well as other three core temperatures, compared with blood temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…[83][84][85][86] Oral, tympanic membrane, and temporal artery thermometers have been compared using the ICU population, but only three studies sampled perianesthesia patients. [86][87][88] Overall, the research on perianesthesia temperature measurement is weak due to a lack of controls, insufficient statistical analysis, and lack of replication. In an effort to reduce complications and costs associated with perioperative hypothermia, it is imperative to maintain normothermia throughout the course of the surgical continuum ( Figure 1).…”
Section: Guideline Intent and Definitionsmentioning
confidence: 98%
“…[83][84][85][86] Oral, tympanic membrane, and temporal artery thermometers have been compared using the ICU population, but only three studies sampled perianesthesia patients. [86][87][88] Overall, the research on perianesthesia temperature measurement is weak due to a lack of controls, insufficient statistical analysis, and lack of replication. In an effort to reduce complications and costs associated with perioperative hypothermia, it is imperative to maintain normothermia throughout the course of the surgical continuum ( Figure 1).…”
Section: Guideline Intent and Definitionsmentioning
confidence: 98%
“…Temporal measurement records the highest temperature from an infrared scan, presumably of the temporal artery. 5 Although this last method is the least invasive, Low et al 6 reported that temporal measurements can underestimate core temperature during athletic events. The goal of each measure is to associate distal temperature measurements with the blood temperature of the hypothalamus, which regulates blood flow to the periphery and shivering for control of body temperature.…”
mentioning
confidence: 99%
“…A temperature difference, or bias of 0.5 C was defined to be clinically acceptable in a study of 41 patients undergoing abdominal and thoracic surgery examining the accuracy of ''deep-forehead'' temperatures compared with PA core temperature. 7 The bias was found to be 0.0 C, with a standard deviation of 0.3 C. Myny and colleagues collected data on 57 orally intubated intensive care unit (ICU) patients with PA catheters and found no significant difference (mean difference 0.14 C; SD 0.51 C) between temporal artery thermometers and PA catheter temperatures. 8 Lawson and colleagues 6 studied 60 adult ICU patients and found that the temporal artery temperatures slightly overestimated the PA temperatures with a mean difference of 20.02 C (SD 0.47 C).…”
Section: Temporal Artery Thermometrymentioning
confidence: 96%
“…5 The studies to date have included PA catheters as a means of measuring core temperature. [6][7][8][9] However, these studies may not necessarily be generalizable to other populations outside of the ICU because PA catheters are usually restricted to ICU settings.…”
Section: Temporal Artery Thermometrymentioning
confidence: 98%